2017
DOI: 10.1186/s12986-017-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on glucose control and insulin sensitivity in subjects with type 2 diabetes: systematic review and meta-analysis

Abstract: Although the regular consumption of resveratrol has been known to improve glucose homeostasis and reverse insulin resistance in type 2 diabetes mellitus (T2DM), the reported results are inconsistent. Thus, we aimed to assess the effects of resveratrol on glycemic control and insulin sensitivity among patients with T2DM. We searched for relevant articles published until June 2017 on PubMed-Medline, Embase, Cochrane Library, and Web of Science. Randomized controlled trials in T2DM patients administered with resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 39 publications
7
84
0
6
Order By: Relevance
“…This is consistent with our previously published hypothesis that resveratrol might improve glucose uptake and/or reduce insulin demand by enhancing vasodilator function in skeletal muscle [39]. A recent meta-analysis has also shown that resveratrol can improve insulin sensitivity and insulin secretion in pancreatic β-cells and increase glucose uptake via Sirtuin-1 or adenosine monophosphate protein kinase mediated pathways [40]. Resveratrol could also facilitate expression of glucose transporter type-4 by acting on estrogen receptors on the endothelium and stimulate skeletal muscle glucose uptake [41], which could be an added metabolic benefit for postmenopausal women.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with our previously published hypothesis that resveratrol might improve glucose uptake and/or reduce insulin demand by enhancing vasodilator function in skeletal muscle [39]. A recent meta-analysis has also shown that resveratrol can improve insulin sensitivity and insulin secretion in pancreatic β-cells and increase glucose uptake via Sirtuin-1 or adenosine monophosphate protein kinase mediated pathways [40]. Resveratrol could also facilitate expression of glucose transporter type-4 by acting on estrogen receptors on the endothelium and stimulate skeletal muscle glucose uptake [41], which could be an added metabolic benefit for postmenopausal women.…”
Section: Discussionsupporting
confidence: 92%
“…Disregarding this special effect, the insulin-sensitizing actions of resveratrol are complex and not completely elucidated. Part of the pharmacodynamic effects of this stilbene compound could derive from its capacity to modulate different pathways and molecular targets, including those downstream of the insulin receptor and mediated by AMP-activated protein kinase (AMPK) and sirtuin 1, as reported in clinical studies on diabetic patients and rodent models of IR, as well as in vitro experimental settings [147][148][149][150][151]. In these studies, treatment with resveratrol has proved to activate both fuel-sensors AMPK and sirtuin 1 in insulin-sensitive peripheral tissues, especially skeletal muscles.…”
Section: Meddiet and Resveratrol In Polycystic Ovary Syndrome (Pcos)mentioning
confidence: 99%
“…Antidiabetic effects of resveratrol have been investigated in recent years. A recent meta-analysis including nine trials has shown a significant reduction in serum levels of fasting glucose, insulin, and insulin resistance following resveratrol supplementation in diabetic patients (Zhu, Wu, Qiu, Yuan, & Li, 2017). Although, some studies reached nonsignificant results (Bashmakov et al, 2014;Goh et al, 2014;Timmers et al, 2016).…”
Section: Introductionmentioning
confidence: 99%